Fundamentalism and censorship in South Asia: Mass misapprehension of Nasrin, Murugan & Rushdie - Nashrif, Islam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.